The level of hand hygiene compliance by operating room personnel of ‎Educational Hospitals in Hamadan University of Medical Science - Mitra Zandiyeh; Seyed Reza Borzo (Journal of Holistic Nursing and Midwifery)
Introduction: Health care associated infections (HCAIs) are among challenges to health care ‎facilities. Hand hygiene is well known as the most efficient, cost benefit and simplest ‎technique for decreasing these infections. In operating room, surgical procedures as invasive ‎techniques affects patients more than patients in other wards. Hence hand hygiene compliance ‎has a substantial importance in these units.